5S System as a Tool for Sustainable Public Sector Governance: A Case Study of Jaffna District Urban Councils in Sri Lanka - Kuganesan, P.; Dilogini, S. (University of Vavuniya, 2024)
The unpredictable political and economic climate in Sri Lanka poses quality issues to the stable continuous and sustainable implementation of the 5S in organizations especially the urban councils. While a number of organizations have been able to implement 5S effectively, the public sector faces microeconomic factors like decreased funding because of COVID-19 and therefore, there is a need for new ways to support and sustain the obtained 5S systems. Nevertheless, few studies have specifics on sustainable 5S implementation practices. Thus, the purpose of this research is to evaluate the current position of 5S sustainability and determine constraining and enabling factors of sustainable 5S implementation within the selected district of Sri Lanka's urban council. This study looks into sustainable aspects of 5S and its implementation. The first research question seeks to know why 5S has not worked well previously, and the second research question aims to know what contributes positively to sustainable 5S in the urban councils of Jaffna. The study uses research paradigm of interpretivism and qualitative research with the use of inductive approach to gather information from the stakeholders involved in the operations of the urban council. Data collection entails purposefully selecting 50 participants from the different levels in the urban councils, that is, from top managerial employees and other members of the community. Self-administered semi-structured interviews are used to determine the following such as perception towards 5S, challenges facing sustainability efforts and possible enhancement. Based on the data analysis, thematic analysis is used to find out about the themes and patterns of 5S sustainability factors. This research enhances the recognition and management of the economic, ecological, and social factors affecting 5S sustainability in enhancing organizational efficiency and operational efficacy within the urban councils.
Keywords: 5S system; Sri Lanka; Sustainability practices; Thematic analysis